Optimalisasi Skrining Tuberkulosis Terintegrasi Kader Kesehatan di Wilayah Kalurahan Sinduharjo Ngaglik Sleman - Wulandari, Dewi Ariyani; Putri Basuki, Prastiwi; Nurwidi Antara, Antok; Puji Prilanty, Intan; Febriani, Mita; Rehi Kalli, Roynaldus (Poltekkes Kemenkes Surakarta, 2025)
Background: The strategy to increase TBC coverage and detection is through Active Case Finding (ACF) through TBC screening training for health cadres. Health cadres who are trained and understand the signs and symptoms of TBC are expected to help increase TBC findings in the community and reduce the stigma of TBC in the community. This community service activity aims to equip cadres with basic TBC screening skillsand equip cadres in implementing ILP Posyandu (Primary Service Integration) management. Methods: The implementation method consists of preparation stage, implementation, training, application of technology, and monitoring and evaluation. Training was given 2 times with assistance. Training on cadre understanding of TBC and TBC screening was attended by 24 cadres and training on ILP Posyandu management was attended by 15 cadres. Results: There was an increase in knowledge and understanding of cadres with lecture and module methods (p value <0.001) and there was an increase in scores before and after the intervention by an average of 3.79 points and there was an increase in cadre skills in implementing ILP Posyandu. In the implementation of integrated TBC screening, Posyandu ILP was enthusiastically attended by 114 community members consisting of 39 infants and toddlers and 75 adults and the elderly. Conclusion: Provision of health cadres will improve cadre knowledge and skills in conducting integrated TBC screening with Posyandu ILP. This activity is recommended to be carried out through continuous training for health cadres to enhance the capacity for integrated tuberculosis screening at the Posyandu ILP.